Effect of Surface Roughness on Corrosion Behavior of GCr15 Bearing Steel in 0.05 mol/L NaCl Solution - WU Xiang-feng, FANG Ke-wei, LI Cheng-tao, LUO Kun-jie, WU Huan-chun, ZHANG Du-bao (Cailiao Baohu, 2021)
The surface roughness is one of important factors that influenced the service life and reliability of bearing steel, but the researches on the relationship between the surface roughness and corrosion resistance of bearing steel has been less reported.Herein, the corrosion behavior of GCr15 bearing steel with different surface roughness Ra(1.35, 1.05, 0.15 μm)in 0.05 mol/L NaCl solution was studied by immersion test, open circuit potential-time(OCP-t)and electrochemical impedance spectroscopy technique(EIS).Results showed that the degree of corrosion of the GCr15 samples with different surface roughness became more severe for the samples with bigger Ra after immersed in 0.05 mol/L for 12 h.For the samples with the Ra values of 1.35 μm and 1.05 μm, the corrosion zones occurred in the scratched gaps regularly, and extended along the gaps.However, for the samples with the Ra value of 0.15 μm, the corrosion zones equally distributed on the surface of samples and seemed like small dots.For the samples with bigger Ra, the open circuit potentials needed more time to reach a relative stable state.Additionally, the samples with different Ra values presented the phenomena of the capacitance reactance at high frequencies and the decreasing impedance at low frequencies.With the increase of Ra, the absolute value of electrochemical impedance was reduced at high frequencies.